Menggali Estetika Ogoh-Ogoh: Simbol Bhuta Kala dan Pesan Sosial dalam Kesenian Bali - Wulandari, Ni Putu Maharani (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Ogoh-Ogoh is a traditional Balinese sculpture that plays an important role in the Nyepi Day celebration. It is a symbol of Bhuta Kala that depicts negative energy that must be neutralized to create harmony. This research aims to explore the aesthetics of Ogoh-Ogoh as a symbol of Bhuta Kala and its social messages, as well as how this art adapts to the social and political context of Balinese society. The research method used is a qualitative approach with thematic analysis through in-depth interviews and observation of the making and parading of Ogoh-Ogoh. The research findings show that Ogoh-Ogoh functions as a religious symbol and a medium of social expression that raises contemporary issues, such as politics, injustice, and social change. In addition, innovations in the form and technique of making Ogoh-Ogoh reflect technological advances and the adaptation of traditional art to the times. This research contributes to providing new insights in studying Balinese art and culture, especially in understanding how Ogoh-Ogoh acts as a profound social communication tool. The results of this study confirm the importance of art as a medium for conveying moral and social messages, as well as the role of art in shaping the collective consciousness of Balinese society.